Legal Certainty In The Role Of The DPRD Functions In Implementing The Right Of Interpelation Based On Constituonal Practices - Anwar - Hidayat (Faculty of Law, Universitas Pekalongan, 2023)
The Regional People's Legislative Council (DPRD) is a legislative institution which is an element of the constitutional structure in our country. This institution functions as a policy initiator, policy supervisor, and works together with the executive to develop joint policies for the welfare of the people. DPRD has many rights in carrying out its duties and functions, one of the many rights is the right of interpellation. The right of interpellation is the right of the DPRD to request information from the government regarding strategic policies that have an impact on social life which certainly affects the development of the nation. The right of interpellation is the right of the DPR/DPRD to ask the government for information regarding important and strategic policies that have an impact on people's lives and the dynamics of the nation. that in forming an Act the DPR cannot proceed alone without the approval of the President. Both of them, both the DPR and the President must agree, the DPR cannot agree but the President does not agree. The two must go hand in hand to agree together.